Effects of Autumn and Spring Heat Waves on Seed Germination of High Mountain Plants. - Simone Orsenigo; Thomas Abeli; Graziano Rossi; Paolo Bonasoni; Cristian Pasquaretta; Maurizia Gandini; Andrea Mondoni (PLoS ONE, 2015)
Alpine plants are considered to be particularly vulnerable to climate change and related extreme episodes, such as heat waves. Despite growing interest in the impact of heat waves on alpine plants, knowledge about their effects on regeneration is still fragmentary. Recruitment from seeds will be crucial for the successful migration and survival of these species and will play a key role in their future adaptation to climate change. In this study, we assessed the impacts of heat waves on the seed germination of 53 high mountain plants from the Northern Apennines (Italy). The seeds were exposed to laboratory simulations of three seasonal temperature treatments, derived from real data recorded at a meteorological station near the species growing site, which included two heat wave episodes that occurred both in spring 2003 and in autumn 2011. Moreover, to consider the effect of increasing drought conditions related to heat waves, seed germination was also investigated under four different water potentials. In the absence of heat waves, seed germination mainly occurred in spring, after seeds had experienced autumn and winter seasons. However, heat waves resulted in a significant increase of spring germination in c. 30% of the species and elicited autumn germination in 50%. When heat waves were coupled with drought, seed germination decreased in all species, but did not stop completely. Our results suggest that in the future, heat waves will affect the germination phenology of alpine plants, especially conditionally dormant and strictly cold-adapted chorotypes, by shifting the emergence time from spring to autumn and by increasing the proportion of emerged seedlings. The detrimental effects of heat waves on recruitment success is less likely to be due to the inhibition of seed germination per se, but rather due to seedling survival in seasons, and temperature and water conditions that they are not used to experiencing. Changes in the proportion and timing of emergence suggest that there may be major implications for future plant population size and structure.